Regional competitiveness in Peninsular Malaysia / Rasidah A. Rahman - A. Rahman, Rasidah (Institute of Graduate Studies, UiTM, 2017)
In recent years, competitiveness has become an important issue in the modern world as many cities have confronted a more precarious competition from cities of home or foreign countries. Kresl and Ietri (2012) believed if there were no competition, regions would not be as efficient and there would not be any pressure for improvements. Malaysia witnessed a change in development paradigm of the federal government with a strong emphasis on building towards a competitive region, thus, in 2006, the five economic corridors were introduced, three in Peninsular Malaysia; The Northern Corridor Economic Region (NCER), Iskandar Malaysia and East Coast Economic Region (ECER). The three economic corridors, with statutory bodies empowered to administer, have put so much effort to promote their own region and to lure national key projects for foreign direct investments. Whether these regions will be successful or not depends on their competitiveness. The main objective of this research is to evaluate competitiveness and factors influencing the competitiveness of regions in Peninsular Malaysia. Taking the three economic corridors and Klang Valley as the study area, two analyses were conducted, firstly, Shift-Share and Location Quotient (LQ) to evaluate competitiveness, and secondly Structural Equation Model (SEM) to evaluate factors. The findings from the Shift-Share analysis reveal that Klang Valley is the most competitive region in Peninsular Malaysia with services sector as a major contributor to its competitiveness. The share of the services sector in Klang Valley is three times the share of NCER and Iskandar…